Nominal Wage Rigidity and the Rate of Inflation. - Nickell, S; Quintini, G (Centre for Economic Performance, LSE, 2001)
Using the accurate and extensive data available in the UK New Earnings Survey, this paper investigates the extent to which nominal wages are downwardly rigid and whether such rigidity interferes with necessary real wage adjustments when inflation is low. Despite the substantial numbers of individuals whose nominal wages fall from one year to the next, we find that if long-run inflation is one percent higher, the number of individuals with negative real pay growth increases by around 1.4 percent. This is controlling for the median and dispersion of the real wage change distribution.